2013
DOI: 10.1007/s12603-012-0376-6
|View full text |Cite
|
Sign up to set email alerts
|

Selenium is inversely associated with interleukin-6 in the elderly

Abstract: Serum selenium was inversely associated with inflammatory cytokine interleukin-6 among elderly living in long-term care facilities in Taiwan. Monitoring serum selenium should be considered in these institutionalized elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
2
21
0
1
Order By: Relevance
“…With regard to effects that are likely to be primarily mediated through host selenoproteins, there is considerable evidence that a dysregulated innate immune system and cytokine release have the capacity to worsen COVID-19 [ 67 , 68 , 69 ]. In the elderly, who are particularly at risk, selenium deficiency is correlated with higher circulating inflammatory cytokines [ 91 ]. Published data support the hypothesis that selenium adequacy prevents excessive cytokine activation in infectious, inflammatory and oncological models [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to effects that are likely to be primarily mediated through host selenoproteins, there is considerable evidence that a dysregulated innate immune system and cytokine release have the capacity to worsen COVID-19 [ 67 , 68 , 69 ]. In the elderly, who are particularly at risk, selenium deficiency is correlated with higher circulating inflammatory cytokines [ 91 ]. Published data support the hypothesis that selenium adequacy prevents excessive cytokine activation in infectious, inflammatory and oncological models [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the elderly, who are particularly at risk, selenium deficiency is correlated with higher circulating inflammatory cytokines [ 91 ]. Published data support the hypothesis that selenium adequacy prevents excessive cytokine activation in infectious, inflammatory and oncological models [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. In some cases, supra-therapeutic selenium contributed to enhanced adaptive immunity by reinvigorating cytotoxic cells and moderating the release of inflammatory cytokines by the innate immune system [ 14 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, the concentration of interleukin-6 negatively correlated with the concentration of selenium in the group of elderly patients [24]. Not all the studies published, however, have provided consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Chang and Tsai 79 reported that MeHg causes IL-6 production and cytotoxicity simultaneously and Nechemia-Arbely et al 80 found that administration of HgCl 2 to mice results in rapid and substantial elevation in serum IL-6 level concurrent with the development of acute kidney injury. Tseng et al 81 demonstrated that serum selenium is inversely associated with inflammatory cytokine (IL-6) among elderly living in long-term care facilities in Taiwan. Shilo et al 82 observed that selenium supplementation strongly attenuates the blood IL-6 elevation.…”
Section: Discussionmentioning
confidence: 99%